The genomic architecture of resistance to Campylobacter jejuni intestinal colonisation in chickens - Psifidi, A.; Fife, M.; Howell, J.; Matika, O.; van Diemen, P.M.; Kuo, Richard; Smith, J.; Hockling, P.M.; Salmon, N.; Jones, M.A.; Hume, D.A.; Banos, G.; et al. (BIOMED, 2016)
Campylobacter is the leading cause of foodborne diarrhoeal illness in humans and is mostly acquired from consumption or handling of contaminated poultry meat. In the absence of effective licensed vaccines and inhibitors, selection for chickens with increased resistance to Campylobacter could potentially reduce its subsequent entry into the food chain. Campylobacter intestinal colonisation levels are influenced by the host genetics of the chicken. In the present study, two chicken populations were used to investigate the genetic architecture of avian resistance to colonisation: (i) a back-cross of two White Leghorn derived inbred lines [(61 x N) x N] known to differ in resistance to Campylobacter colonisation and (ii) a 9th generation advanced intercross (61 x N) line.